2022
DOI: 10.46827/ejpe.v9i1.4479
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Playing Chess on Cognitive Skills in Schools Under Chess Association of Ampara District, Sri Lanka

Abstract: The primary purpose of this study is to investigate the impact of playing chess on cognitive skills in schools under the chess association of Ampara district. A quantitative research approach was followed to analyze that respective objective under the chess association of Ampara district and identify the strategies chess players and coaches can take to improvise the impact of playing chess among the school students. Thirty students as an experimental group and thirty students as an control group from schools p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Chess is a very popular intellectual nongambling game due to its proven benefits for: i) the development of logical thinking (that is of great importance for elementary school children possessing poorly developed logics [25,26]) and emotional-volitional sphere; ii) fostering team collaboration and friendship-building among children; iii) and furthermore, chess can serve as an interesting hobby, as well as a strong protective factor against stress [4][5][6]44]. Also, many studies showed that playing chess positively correlates with children's academic performance at school [7,8,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chess is a very popular intellectual nongambling game due to its proven benefits for: i) the development of logical thinking (that is of great importance for elementary school children possessing poorly developed logics [25,26]) and emotional-volitional sphere; ii) fostering team collaboration and friendship-building among children; iii) and furthermore, chess can serve as an interesting hobby, as well as a strong protective factor against stress [4][5][6]44]. Also, many studies showed that playing chess positively correlates with children's academic performance at school [7,8,45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the large number of available academic papers investigating the impact of chess on the cognitive abilities of children, youth and adults [4][5][6]44], little is known of the role of physical exercises on intellectual functions of young chess players. In turn, a study of the cognitive functions of video game players by Sanz-Matesanz M. and co-authors showed that the athletes usually have good physical activity, but it was difficult to establish its effect on in-game performance et al,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation